Association of Sociodemographic Factors in Affecting the Knowledge, Attitude, and Behaviour of Tuberculosis and HIV in Malang: A Community-Based Study in Rural Area - Rosandy, Milanitalia; Candradikusuma, Didi; Indiastari, Dewi; Fatma, Endah; Budiarti, Niniek; Sutanto, Heri; Abellia, Gaby (Universitas Brawijaya, 2024)
Background: Tuberculosis is the leading cause of death among people with HIV. In Indonesia, the Tuberculosis prevalence in 2021 stood at 969,000 cases with an average of 354 cases per 100,000 people. Nevertheless, tuberculosis is often neglected by many people, whereas in fact, it is a preventable and curable disease. This study aims to assess the knowledge, perception, behaviour, and screening for tuberculosis and their association with sociodemographic factors in a rural area of Malang, Indonesia. Method: A cross-sectional community-based study was conducted. The subjects of this study were adults (≥18 years old) who could comprehend the Indonesian language. We included 462 individuals who were chosen randomly by a multistage stratified sampling technique in rural areas of Malang, Indonesia. A validated questionnaire was asked to be filled in by participants, which were selected randomly using a multistage stratified sampling technique. Collected data were analyzed on SPSS for Windows version 25.0 Results: This study found that most (59.77%) of adults from the study area are still unaware of tuberculosis infection, transmission, prevention, and its risk factors. Only 1.2% were aware of the importance of screening if they had contact with positive tuberculosis patients. Participants in the age groups of 61 to 70 and over 70 years old were 5.5 and 4.0 times more likely to exhibit unsatisfactory behaviour compared to those in the 27 to 30 age group. Conclusion: This study shows that knowledge, perceptions, behaviours and tuberculosis screening toward tuberculosis are still lacking in rural communities in Malang and showed that participant on younger age and higher educational subjects has better knowledge, behaviour, perception and screening towards Tuberculosis and HIV.